Implementation of Religious Guidance during the Covid-19 Pandemic Period at Women's Penitentiary Class IIA Palembang - Aprillia; Maimunah; Achmad Syarifudin (HM Publisher, 2022)
This study aims to determine the implementation of religious development during the Covid-19 period and the difference between before and after the Covid-19 pandemic in Class II A prisons in Palembang. The research method used is field research using interview, observation, and documentation data collection techniques. The data analysis method used is the Miles and Huberman analysis method using the stages, namely data reduction, data presentation, and conclusions. The results of the study revealed that the implementation of religious guidance during the Covid-19 period at the Class II A Penitentiary in Palembang was carried out virtually. For certain conditions, face-to-face meetings are also carried out but still follow health protocols. Meanwhile, the implementation of religious guidance in the period before the Covid-19 pandemic was carried out face-to-face. The practice of worship during the pandemic is not optimal because the supervisor has difficulty providing direct practice when delivering the material.